2011
DOI: 10.1371/journal.pone.0015712
|View full text |Cite
|
Sign up to set email alerts
|

Individualized and Clinically Derived Stimuli Activate Limbic Structures in Depression: An fMRI Study

Abstract: ObjectivesIn the search for neurobiological correlates of depression, a major finding is hyperactivity in limbic-paralimbic regions. However, results so far have been inconsistent, and the stimuli used are often unspecific to depression. This study explored hemodynamic responses of the brain in patients with depression while processing individualized and clinically derived stimuli.MethodsEighteen unmedicated patients with recurrent major depressive disorder and 17 never-depressed control subjects took part in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 33 publications
4
44
0
Order By: Relevance
“…For example, multiple groups have reported trauma-related changes to the medial temporal gyrus, with its putative role in integrating memory function and imagery (e.g., Shin et al, 2001; Dickie et al, 2008; Moores et al, 2008). The lingual gyrus, with its likely role in visual processing and integration, has also been implicated in imaging studies of depression, conflict resolution, and impaired reward response (Dichter et al, 2009; Kessler et al, 2011; Chechko et al, 2013), whereas the postcentral gyrus has been associated with depression and pain (Bar et al, 2007). Taken together, we interpret this to mean that thalamic hyperconnectivity is associated with broad-based disruptions between important brain functions, inclusive of salience, memory and visual processing and sensation, that corresponds to both the literature and our clinical experience with this population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple groups have reported trauma-related changes to the medial temporal gyrus, with its putative role in integrating memory function and imagery (e.g., Shin et al, 2001; Dickie et al, 2008; Moores et al, 2008). The lingual gyrus, with its likely role in visual processing and integration, has also been implicated in imaging studies of depression, conflict resolution, and impaired reward response (Dichter et al, 2009; Kessler et al, 2011; Chechko et al, 2013), whereas the postcentral gyrus has been associated with depression and pain (Bar et al, 2007). Taken together, we interpret this to mean that thalamic hyperconnectivity is associated with broad-based disruptions between important brain functions, inclusive of salience, memory and visual processing and sensation, that corresponds to both the literature and our clinical experience with this population.…”
Section: Discussionmentioning
confidence: 99%
“…Buchheim et al (2008) have investigated the attachment system, important in some psychological disorders and psychotherapy treatments, in borderline personality disorder. Kessler et al (2011) and Loughead et al (2010) probed neural systems involved in processing of interpersonal relationship patterns and autobiographical interpersonal memories, central to understanding self and interpersonal schema, therapeutic alliance, and conduct of many types of psychotherapy, especially psychodynamic therapies. An interesting functional connectivity study of an affective listening task, highly relevant to listening behaviors during psychotherapy sessions, showed that activation of right amygdala, insula, and auditory cortex preceded activations in homologous regions in the left hemisphere, while left auditory cortex activation preceded right amygdala decreases (Tschacher, Schildt, & Sander, 2010).…”
Section: Effects Of Psychotherapy On the Brain: A Selective Reviewmentioning
confidence: 99%
“…Brought to you by | University of Windsor Authenticated Download Date | 10/7/15 9:46 AM Recently some authors reported neurobiological and (in some cases also) clinical changes in different kinds of subjects treated with psychodynamic psychotherapy (Overbeck et al, 2004;Saarinen et al, 2005;Lai et al, 2007;Lehto et al, 2008;Beutel et al, 2010;Kessler et al, 2011;Buchheim et al, 2012;de Greck et al, 2013;Gawrysiak et al, 2013;Kehyayan et al, 2013;Taubner et al, 2013).…”
Section: Backgroundsmentioning
confidence: 99%